YES OR NO? GOOGLE TRANSLATE FOR EFL ONLINE WRITTEN DISCUSSION - Angela Bayu Pertama Sari; Sri Rejeki; Dwi Iswahyuni; Devita Widyaningtyas Yogyanti (PROJECT (Professional Journal of English Education), 2023)
Online written discussion is a difficult skill for some students because of the need for more vocabulary and the time constraint in expressing their ideas. Thus, this research aims to further the use of Google Translate in EFL online written discussions. This research was conducted in one private university in Yogyakarta, Indonesia, involving 134 respondents. Then researchers distributed open-ended questionnaires as the data collecting technique. The research revealed that the students used Google Translate for four different needs: for word translation, for grammar and spelling checker, for quick translation, and for arranging words into good sentences. The translation machine was the highest use of Google Translate during the online written discussion activity. On the other hand, the research result showed two Google Translate limitations: the inaccuracy of translation results and inauthentic students’ writing. Despite some drawbacks of Google Translate, the students still consider Google Translate as a helpful tool for supporting them in learning English, particularly in online written discussions.